SEROLOGICAL AND MOLECULAR CHARACTERIZATION OF SWINE ROTAVIRUS FROM THE SOUTH REGION OF BRAZIL - KROEFF, Suzana Silveira (Scientia Agraria, 2000)
The purpose of this study was to evaluate serological and molecular characterization of swine rotavirus from the South region of Brazil. For this, 167 swine fecal samples were obtained from 52 farms with historical of diarrhea during weaning and post-weaning period. In 14 regions from Rio Grande do Sul, Santa Catarina and Paraná states between June 1995 and October 1997. All samples were tested in a enzyme-linked immunosorbent assay (ELISA) to detect group A rotavirus, where 59 (35.33%) samples were positive. Poliacrilamide gel electrophoresis (PAGE) test was revealed only one electropherotype of swine rotavirus. Positive samples were tested in an ELISA using monoclonal antibodies to characterize subgroup, where 9 samples were specific for subgroup II and 50 samples did not react for tested subgroups (nonl-nonII). Rotavirus G and P genotypes were characterized by reverse transcription followed by polymerase chain reaction (RT-PCR) with specific primers for swine, bovine and human. Samples were defined as genotypes G3, G4, G5, G9 and G10. P genotype identified where P[6], P[7] and mixtures of P[6] and P[7] occurring simultaneously in the same animal. This study showed presence of different swine rotavirus genotypes circulating in same region and/or same farm, including G9 genotype, not yet described in swine samples.